2010
DOI: 10.1007/978-3-642-15892-6_24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Gesture and Language on Personality Perception in Conversational Agents

Abstract: Abstract. A significant goal in multi-modal virtual agent research is to determine how to vary expressive qualities of a character so that it is perceived in a desired way. The "Big Five" model of personality offers a potential framework for organizing these expressive variations. In this work, we focus on one parameter in this model -extraversion -and demonstrate how both verbal and non-verbal factors impact its perception. Relevant findings from the psychology literature are summarized. Based on these, an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 27 publications
4
93
0
Order By: Relevance
“…Recently, Neff et al [26] examined the combined effect of linguistic and nonverbal expression of personality for the Extraversion trait of the Big Five. Previously, Isbister & Nass [19] presented the only other work we are aware of to explore the combined gestural and linguistic expression of personality, also focusing on extraversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Neff et al [26] examined the combined effect of linguistic and nonverbal expression of personality for the Extraversion trait of the Big Five. Previously, Isbister & Nass [19] presented the only other work we are aware of to explore the combined gestural and linguistic expression of personality, also focusing on extraversion.…”
Section: Discussionmentioning
confidence: 99%
“…Yet it remains an open challenge as to how to imbue an agent with these qualities and how to organize the underlying range of expressive variation. The "Big Five" or "OCEAN" model of personality represents an appealing organizing framework [5,23,22,26]. The model has emerged as a standard in psychology, with research over the last fifty years systematically documenting correlatons between a wide range of behaviors and the Big Five traits (extraversion, neuroticism/emotional stability, agreeableness, conscientiousness, openness to experience) [24,30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Salem et al [5] found that a robot is evaluated more positively when non-verbal behaviors such as hand and arm gestures accompany speech. Neff et al [9,10] conducted experiments to understand how the Big Five traits of emotional stability and extraversion correlate with changes in verbal and nonverbal behavior. The perception of these traits is varied by adjusting a virtual agent's gesture rate, whether self-adaptors are present and movement style parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Their gestures are also more frequent and animated than the gestures of introverts [11]. Findings such as these have been applied to agents designed to portray extraversion [15].…”
Section: Seeing Personalitymentioning
confidence: 99%